2017
DOI: 10.1186/s12933-017-0591-x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse associations between serum levels of secreted frizzled-related protein-5 (SFRP5) and multiple cardiometabolic risk factors: KORA F4 study

Abstract: AimsSecreted frizzled-related protein (Sfrp)5 has beneficial effects on insulin sensitivity, inflammation and cardiovascular risk in different mouse models, but its relevance for cardiometabolic diseases in humans is controversial. We aimed to characterise associations of circulating SFRP5 with cardiometabolic risk factors and prediabetes/type 2 diabetes in a large population-based cohort.MethodsCross-sectional associations between serum SFRP5 and cardiometabolic risk factors as well as prediabetes/type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
6
36
0
Order By: Relevance
“…Hu ZP et al 36 found that circulating plasma concentrations of SFRP5 were decreased in T2DM patients compared with healthy controls and they were negatively correlated with homeostasis model assessment of insulin resistance, suggesting that SFRP5 might exert a protective effect on the mechanism of T2DM. Similar results were observed by clinical studies conducted by Hu WJ et al, 38 Cheng et al 48 and Carstensen-Kirberg et al, 49…”
Section: S Frp5 In the Pathogenesis Of T2dmsupporting
confidence: 88%
See 1 more Smart Citation
“…Hu ZP et al 36 found that circulating plasma concentrations of SFRP5 were decreased in T2DM patients compared with healthy controls and they were negatively correlated with homeostasis model assessment of insulin resistance, suggesting that SFRP5 might exert a protective effect on the mechanism of T2DM. Similar results were observed by clinical studies conducted by Hu WJ et al, 38 Cheng et al 48 and Carstensen-Kirberg et al, 49…”
Section: S Frp5 In the Pathogenesis Of T2dmsupporting
confidence: 88%
“…Hu ZP et al found that circulating plasma concentrations of SFRP5 were decreased in T2DM patients compared with healthy controls and they were negatively correlated with homeostasis model assessment of insulin resistance, suggesting that SFRP5 might exert a protective effect on the mechanism of T2DM. Similar results were observed by clinical studies conducted by Hu WJ et al, Cheng et al and Carstensen‐Kirberg et al, and all indicated a possible role for SFRP5 as a protective factor in the pathogenesis of T2DM. In contrast, Canivell et al observed that circulating plasma levels of SFRP5 were augmented in patients with T2DM compared with prediabetic patients and healthy controls.…”
Section: Sfrp5 In the Pathogenesis Of T2dmsupporting
confidence: 88%
“…The measurement of serum lipids was done as described, the assessment of kidney function from the estimated glomerular filtration rate (eGFR) was based on the chronic kidney disease epidemiology creatinine equation.…”
Section: Study Participants and Methodsmentioning
confidence: 99%
“…Measurement methods of glucose, insulin and HbA 1c , and calculation of the homeostasis model assessment of insulin resistance (HOMA-IR) and whole-body insulin sensitivity index (composite) were also reported before. [27][28][29] The measurement of serum lipids was done as described, 27,30 the assessment of kidney function from the estimated glomerular filtration rate (eGFR) was based on the chronic kidney disease epidemiology creatinine equation.…”
Section: Assessment Of Anthropometric Metabolic Lifestyle and Immentioning
confidence: 99%
“…Secreted frizzled protein‐5 (SFP5) is secreted from various tissues including visceral, subcutaneous, pericardial adipose tissues, liver, heart, pancreatic islets, and mononuclear blood cells . Different cross‐sectional clinical studies have found that SFP5 serum levels are inversely related to diabetes and cardiovascular disease risk factors, and its concentration is lower in prediabetes or T2DM . Treatment with Liraglutide increased SFP5 levels .…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 99%